L-glutamine in vitro supplementation enhances Nile tilapia Oreochromis niloticus (Linnaeus, 1758) leukocyte function - Carvalho, Pedro L. P. F. [UNESP]; Yamamoto, Fernando Y.; Barros, Margarida M. [UNESP]; Gatlin, Delbert M. (Elsevier B.V., 2018)
Under appropriate conditions, glutamine (Gln) is an essential nutrient for immunological responses, acting as a metabolic substrate for proliferation of enterocytes and lymphocytes, and having positive effects on the function of stimulated immune cells. Thus, specific components of both innate and adaptive immune systems of Nile tilapia were evaluated after supplementing Gln to cell culture media. Primary cell cultures of kidney leukocytes were used for respiratory burst and phagocytic activity assessment. The ability of macrophages to kill Streptococcus iniae also was evaluated. Additionally, a proliferation assay was conducted with peripheral blood lymphocytes (PBL) exposed to non-specific mitogens. Results showed that macrophage phagocytosis, anion superoxide production, and bactericidal capacity were significantly (P < 0.05) enhanced by Gin supplementation to the culture media. The proliferation of lymphocytes upon mitogenic exposure also was significantly (P < 0.05) enhanced by Gin supplementation to the media. Our results suggest that in vitro, different levels of Gin were necessary for optimal immunological responses of leukocytes and lymphocytes. As such, Gin supplementation was able to enhance and modulate both innate and adaptive responses of Nile tilapia leukocytes, highlighting its potential application as an immunonutrient.
Keywords: In vitro assays; Lymphocyte proliferation; Macrophages; Nile tilapia; Phagocytosis